Yesterday's Deterrent : Tirpitz and the Birth of the German Battle Fleet - Steinberg, Jonathan (London Macmillan, 1968)
Social and historical background of Germany's World War 1 navy, based on the official German archives.
Include Illustration, Appendix and Index
Keywords: Germany. Kriegsmarine -- Tirpitz, Alfred von, 1849-1930